Evaluation of the shear adhesion strength of impact ice by a new method - Wang, Yusong; Xiong, Ke; Zhu, Chunling; Zhu, Chengxiang; Chen, Lei (Engineering fracture mechanics, 2023)
•A new and high-precision test bench for the shear adhesion strength of ice-substrate interface is obtained.•The subject of this paper is impact ice and the experiments are performed in an icing wind tunnel, which makes the results close to the practical situation.•Glaze ice demonstrates a rise in its shear adhesion strength at lower temperatures, while the change trend is the opposite for rime ice.•The growing liquid water content (LWC), rough surfaces, and surface painting will enhance the interface adhesion.•Superhydrophobic surfaces have proven to possess a significant reduction in adhesion strength at higher temperature. Aircraft icing has a detrimental effect on flight safety. The design of aircraft anti-icing/de-icing systems requires a thorough comprehension of the adhesion between the ice and the substrate. In this research, the multi-hole rotating cylinder method (MHRC) is developed in an icing wind tunnel. Simulations of interfacial stress show that ice thickness does not change the evenness of stress, whereas reducing the contact area can impair uniformity. Moreover, the ice layer would not experience any cohesive damage during the experiments. The shear ice adhesion strength is evaluated using the methodology outlined in this research. At lower temperatures, glaze ice demonstrates a rise in its shear adhesion strength, while the change trend is the opposite for rime ice. The lowest adhesion strength is observed at the medium volume diameter (MVD) of 45 µm. Furthermore, the growing liquid water content (LWC), rough surfaces, and surface painting will enhance the interface adhesion of ice to the substrate to varying degrees. Stainless steel substrate exhibits higher adhesion strength with ice as compared to aluminum and titanium. In addition, superhydrophobic surfaces have proven to possess a significant reduction in adhesion strength at higher temperature. The proposed experimental method and platform afford accurate measurements of the shear adhesion strength of impact ice in the icing wind tunnel.